Transcending conventional credentialing and assessment paradigms with information-rich digital badges. Issue 2 (14th March 2016) - Casilli, Carla; Hickey, Daniel
ABSTRACT: Open digital badges are Web-enabled tokens of learning and accomplishment. They operate in an environment of explicit (rather than tacit) trust; open badges provide issuers the ability to include specific claims and associate those claims with detailed supporting evidence. Earners are encouraged to share their badges over social networks, e-mail, and websites, and the information they contain is expected to circulate readily in these spaces. Building upon current concepts and theories from the Information Sciences and Learning Sciences, this article shows how the informational affordances of digital badges are transforming education and learning more generally, and more particularly by transcending conventional paradigms of academic credentialing and educational assessment.